A matter of origin - identification of SEMA3A, BGLAP, SPP1 and PHEX as distinctive molecular features between bone site-specific human osteoblasts on transcription level - Zhang, Weiping; Rau, Sibylle; Kotzagiorgis, Konstantinos; Rothweiler, René; Nahles, Susanne; Gottwald, Eric; Rolauffs, Bernd; Steinberg, Thorsten; Nelson, Katja; Altmann, Brigitte (Frontiers in Bioengineering and Biotechnology, 2022)
In oral and maxillofacial bone reconstruction, autografts from the iliac crest represent the gold standard due to their superior clinical performance, compared to autografts derived from other extraoral regions. Thus, the aim of our study was to identify putative differences between osteoblasts derived from alveolar (hOB-A) and iliac crest (hOB-IC) bone of the same donor (nine donors) by means of their molecular properties in 2D and 3D culture. We thereby focused on the gene expression of biomarkers involved in osteogenic differentiation, matrix formation and osteoclast modulation. Furthermore, we examined the transcriptional response to Vit.D3 in hOB-A and hOB-IC. Our results revealed different modulation modes of the biomarker expression in osteoblasts, namely cell origin/bone entity-dependent, and culture configuration- and/or time-dependent modulations. SEMA3A, SPP1, BGLAP and PHEX demonstrated the strongest dependence on cell origin. With respect to Vit.D3-effects, BGLAP, SPP1 and ALPL displayed the highest Vit.D3-responsiveness. In this context we demonstrated that the transcriptional Vit.D3-response concerning SPP1 and ALPL in human osteoblasts depended on the cell origin. The results indicate a higher bone remodeling activity of iliac crest than alveolar osteoblasts and support the growing evidence that a high osteoclast activity at the host-/donor bone interface may support graft integration.